Chapter Employability and Transitions: Fostering the Future of Young Adult Graduates - Boffo, Vanna (Studies on Adult Learning and Education, 2018)
Starting from questions inspired by the tremendous changes taking place in the worlds of education and employment, this research focuses on the role of employability in the building of new skills in higher education contexts. This longitudinal survey conducted on a sample of 52 graduates from the Educational Science sector found certain key characteristics in the transitions to the world of work, allowing reflection on those educational activities whose impact is more favourable to develop job placement